PUDING WUNGU Graptophyllum pictum L Griff LEAVES SIMPLICIA STANDARDIZATION - Desi Sagita; Barmi Hartesi; Yuli Fitri Utami (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Puding wungu leaves Graptophyllum pictum (L.) Griff have potential activity for laxative, diuretic, antiinflammation and antibacterial. Those Puding wungu leaves potential to be developed as an active ingredient in pharmaceutical products. This study aims to standardize the simplicia of puding wungu. There are two parameters for standardization, ie. Specific parameter and non specific parameters. Specific parameters include macroscopic, microscopic testing, determination of chemical content, water-soluble and ethanol-soluble content and non-specific parameters include total ash content, acid-insoluble ash content, water content, and dry shrinkage. The method for standardization refers to Harborne methods and general standard method in Ministry of Health of republic Indonesia books. Puding wungu leaves have an oval shape, the edge of leaf is regular, distinctive odor, a brownish-purpe color, pinnate leaf, shiny surface, the tip and base of the leaf is tapered. Puding wungu leaves contain tannin, flavonoids, steroids, alkaloids and phenollic compounds. Water soluble content of 34.54%, ethanol soluble content 13.07% ± 0.02; ash content 7.06% ± 0.01; acid insoluble ash content 1.77% ± 0.02; water content 0.21% ±0.05, and drying loss 2.90% ± 0.17. All standardization parameters meet the requirement of raw material from Pharmacopeae herbal Indonesia, Materia medica or standard set by the government.